Composite Resin to Yttria Stabilized Tetragonal Zirconia Polycrystal Bonding: Comparison of Repair Methods - Cristoforides, P. [UNESP]; Amaral, R. [UNESP]; May, L. G.; Bottino, M. A. [UNESP]; Valandro, L. F. (Operative Dentistry Inc, 2012)
Purpose: The purpose of the current study was to evaluate different approaches for bonding composite to the surface of yttria stabilized tetragonal zirconia polycrystal (Y-TZP) ceramics.Methods: One hundred Y-TZP blocks were embedded in acrylic resin, had the free surface polished, and were randomly divided into 10 groups (n=10). The tested repair approaches included four surface treatments: tribochemical silica coating (TBS), methacryloxydecyldihidrogenphosphate (MDP)-containing primer/silane, sandblasting, and metal/zirconia primer. Alcohol cleaning was used as a "no treatment" control. Surface treatment was followed by the application (or lack thereof) of an MDP-containing resin cement liner. Subsequently, a composite resin was applied to the ceramic surface using a cylindrical mold (4-mm diameter). After aging for 60 days in water storage, including 6000 thermal cycles, the specimens were submitted to a shear test. Analysis of variance and the Tukey test were used for statistical analyses (alpha=0.05).Results: Surface treatment was a statistically significant factor (F=85.42; p<0.0001). The application of the MDP-containing liner had no effect on bond strength (p=0.1017). TBS was the only treatment that had a significantly positive effect on bond strength after aging.Conclusion: Considering the evaluated approaches, TBS seems to be the best surface treatment for Y-TZP composite repairs. The use of an MDP-containing liner between the composite and Y-TZP surfaces is not effective.